PENINGKATAN KINERJA DAN KOMPETENSI GURU DALAM PENGELOLAAN PEMBELAJARAN MELALUI BIMBINGAN BERKELANJUTAN DI SD 2 REJOSARI PADA SEMESTER 1 TAHUN PELAJARAN 2018/2019 - Bambang Sutopo Bambang Sutopo (Universitas PGRI Yogyakarta, 2020)
Abstract Background; 1) teacher performance and competence in learning management are low. 2) the teacher does not understand 4 main competencies, namely pedagogical, personality, social, and professional competencies. 3) teachers are not yet skilled in preparing learning plans, 4) teachers are not yet skilled in effective learning management. The research objective is to improve the performance and competence of Rejosari Elementary 2 teachers in the management of learning through ongoing guidance.This research was conducted in semester 1 of 2018/2019 Academic Year, namely July-December 2018 at SD 2 Rejosari, UPT Education District of Dawe, Kudus Regency, with 10 teachers as research subjects. Sources of data obtained through documentation, observation and interviews. Comparative qualitative descriptive data analysis followed by reflection with School Action Research action procedures in two cycles, each cycle performed in 3 meetings.Research result; 1) The percentage of teacher performance in learning management in the initial condition is 65% sufficient category, 75% in the first cycle is enough, and 88% in the second cycle is good. 2) The percentage of teacher competency in learning management in the initial condition is 60% less category, 73% in the first cycle is enough, and 88% in the second cycle is good.Keywords: Performance, Teacher Competence and Continued Guidance.